PERKEMBANGAN PENELITIAN HUTAN RAKYAT DI INDONESIA: TINJAUAN BIBLIOGRAFI: The Development of Community Forest Research in Indonesia: Bibliography Review (Jurnal ForestrIndo, 2025)
Private forests in Indonesia have an essential role in ensuring communities’ survival. The science of private forest management is necessary for achieving sustainable forest management. However, the science of private forest management is still relatively young compared to the forest management sciences intended to manage large and massive forests. Therefore, it is important to know to what extent the development of the science of private forest management has been through various studies over the years. The objective of this research is to map the development of research in the private forests from year to year, covering the location of research, publications, themes, and sub-themes starting from 2013-2023 as well as to find out the correlation between the theory and practice of private forest management. The research was conducted using bibliographic surveys and analyzed qualitatively descriptively, as well as an annotated bibliography. The research results show that a lot of private forest research is done in West Java Province, with the themes of production and planting sub-themes. Some practices in the field do not apply theory, so private forest management has yet to reach optimum.